RECLAMATION OF FORMER COAL MINING LAND AT THE NORTHERN PIT OF CV. SEMOGA SURYA SENTOSA, SELUANG RIVER, SAMBOJA, EAST KALIMANTAN - Yustina Hong Lawing; Merdi Handayani (PT. Jurnal Center Indonesia Publisher, 2026)
The rehabilitation of post-mining land with low nutrient content is carried out using chemical and organic materials. To improve soil fertility, the application of fertilizers is required. Soil fertility is crucial as a medium for plant growth to enable replanting. Once the planting medium is available, it is then cultivated with plants suitable for the land conditions. The methodology of this study involved observing land conditions by examining soil structure, texture, and pH in the research area. The results showed that the soil texture belongs to the sandy clay loam or clay loam class, with a soil pH of 3.72. Soil improvement was carried out by applying dolomite lime at 100 grams per planting hole, requiring a total of 66.7 kilograms. Goat manure was applied at 2 kilograms per planting hole, with a total requirement of 133.4 kilograms for 667 trees. The tree species planted were Sengon (Paraserianthes falcataria) and Trembesi (Samanea saman).